Evaluation of Three Different Spreading Forces Using Lateral Condensation Technique on Apical Leakage and Tooth Fracture: An in Vitro Study - Safora Sahebi; Fariborz Moazami; Mohammad reza Nabavizade (Islamic Dental Association of Iran, 2012)
Background and Aim: Lateral condensation technique is one of the most frequently used techniques for root canal obturation. There were few studies in order to determine the needed force for spreader penetration and its effect on apical seal. The  purpose of this study was the in vitro evaluation of the effect of three spreader forces using the lateral condensation technique and the effect of these forces on root fractures. Materials and Methods: Eighty-five human mandibular premolar single rooted teeth without severe curvature and visible fractures were chosen and randomly divided into three groups. Following canal preparation , all samples were obturated on an acrylic model using three forces (1.6, 3 and 4.5 kg) with the lateral condensation technique. The teeth were ob- served under the stereomicroscope ×6 for any fracture line and follow the clearing of the teeth the maximum dye leakage penetration was measured for each tooth. The data were analyzed by using chi-square and Kruskal Wallis statistical tests. Results: All samples in the positive control group showed dye leakage but in the negative control group no sample showed any leakage. The mean dye penetration for the first (1.6 kg), second (3kg) and third (4.5 kg) groups was 0.344 mm, 0.153 mm and 0.746 mm, respectively. The 3kg force for lateral condensation technique produced a significantly better apical seal and less leakage in comparison with the other groups (P<0.05) and more fractures were observed with 4.5kg force (P<0.05). Conclusion: The best force for lateral condensation in premolar teeth was 3kg and  more pressure could produce more fracture.